Mastering Qt 5 programming - Hoff, Benjamin (Packt, 2018)
"Qt is a powerful, cross-platform, graphics development framework. It provides a large set of consistent, standardized libraries and works on many major platforms, including embedded, mobile, desktop, and the web. In this course, we will cover advanced Qt topics. This includes an in-depth dive into custom model-views, showcasing the power and flexibility of the model-view architecture. We will also work with Qt's web offerings, learning how to extend applications by using the World Wide Web. This course also looks into multimedia capture/manipulation (both sound and video), which play key roles in the mobile arena. Continuing the mobile trend, you will be walked through Qt's mobile offerings, including QtQuick, QML, and communicating between C++ and QML. With the advanced concepts of mobile covered, you will explore animations, graphical effects, and 3-dimensional manipulation. Towards the end of this course, you will be able to harness advanced models, 3D, the web, and multimedia to build user interfaces, starting from development all the way to cross-platform distribution."--Resource description page